2016
DOI: 10.1109/lsp.2016.2614693
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Power Allocation for OFDMA Systems under I/Q Imbalance

Abstract: Abstract-Direct-conversion architectures can offer highly integrated low-cost hardware solutions to communication transceivers. However, it has been demonstrated that radio frequency (RF) impairments, such as amplifier nonlinearities, phase noise and in-phase/quadrature-phase imbalances (IQI), can lead to a severe degradation in the performance and fairness. To this end, we study the power allocation (PA) problem in an orthogonal frequency-division multiple access (ODFMA) system, when the served user equipment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Rather than this, the investigation of the proposed in methods under the assumption of OFDM and/or carrier aggregations is also challenging [187,188]. Furthermore, since the hardware of the low-cost relay nodes is most likely to be of poor quality, relays are more prone to hardware imperfections [189][190][191][192][193]. Also, when SWIPT is applied, energy harvesting is performed at a cost on the signal quality used for detection.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than this, the investigation of the proposed in methods under the assumption of OFDM and/or carrier aggregations is also challenging [187,188]. Furthermore, since the hardware of the low-cost relay nodes is most likely to be of poor quality, relays are more prone to hardware imperfections [189][190][191][192][193]. Also, when SWIPT is applied, energy harvesting is performed at a cost on the signal quality used for detection.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than this, the investigation of the proposed in methods under the assumption of OFDM and/or carrier aggregations is also challenging [182,183]. Furthermore, since the hardware of the low-cost relay nodes is most likely to be of poor quality, relays are more prone to hardware imperfections [184]. Also, when SWIPT is applied, energy harvesting is performed at a cost on the signal quality used for detection.…”
Section: Discussionmentioning
confidence: 99%
“…It is recalled here that for practical analog RF front-end electronics, the values of IRR t is typically in the range of 20 dB − 40 dB [256,257,292,299,333,345,[352][353][354][355][356][357][359][360][361][362]. From (4.5), it is observed that the base band equivalent transmitted signal in the presence of IQI can be obtained as…”
Section: Up-conversion In the Presence Of Iqimentioning
confidence: 99%